REDUCING GREENHOUSE GAS (GHG) EMISSIONS THROUGH SOLAR CELL PHOTOVOLTAIC PLANNING AT AL-JIHAD ISLAMIC BOARDING SCHOOL IN SURABAYA - Auvaria, Shinfi Wazna; Agung, Tri Sunan; Ruwantari, Ira Nur; Karami, Abdillah Akmal (Journal of Environmental Engineering and Sustainable Technology, 2024)
Currently, 80% of conventional energy is used to meet the needs of industry and the general public. Using new, renewable energy from the sun is an effort to mitigate climate change by reducing greenhouse gases (GHG). Al-Jihad Boarding School, an Islamic educational institution with around 1,200 students, is one of the biggest consumers of conventional energy. This study aims to plan photovoltaic solar cells, calculate the amount of power that can be generated, calculate the amount of GHG emission reduction from photovoltaic solar cells and the costs required for installation at Al-Jihad Islamic Boarding School. The planning results were analyzed by adjusting the selection of a 12 KVA inverter, 44 polycrystalline photovoltaic solar cells, and other complementary materials such as cables, MCBs and supports. The amount of power generated from photovoltaic solar cells at the Al-Jihad Islamic Boarding School in Surabaya is 12 kWh. Climate change mitigation efforts by reducing GHG emissions through solar cell photovoltaic planning at the Al-Jihad Islamic Boarding School in Surabaya can reduce CO2 greenhouse gases by 1,200.5 kg, NH4 30.013 kg, and N2O 0.019 kg. The cost required for the installation of photovoltaic solar cells is Rp. 209,850,400.